5237 Sayılı Türk Ceza Kanununda rüşvet suçu - Kahraman, Recep (My University, 2018)
Bu tezde 5237 sayılı Türk Ceza Kanunu’nun 252 inci maddesinde yer alan rüşvet suçu incelenmektedir. Tez üç bölümden oluşmaktadır. Birinci bölümde, rüşvet suçunun muhatabı olan kamu idaresi kavramı, kamu idaresine karşı işlenen suçların ceza kanunlarında düzenlenişi, genel olarak rüşvet kavramı, rüşvet suçunun türleri, rüşvet suçuyla korunan hukuki yarar, suçun tarihi gelişimi incelenmektedir. Ayrıca birinci bölümde Türk ceza hukuku sisteminde ve mukayeseli hukukta rüşvet suçuna ilişkin güncel hükümlere yer verilmektedir. Tezin ana gövdesi olan ikinci bölümde rüşvet suçunun yapısı ve unsurları tüm detaylarıyla incelenmektedir. İnceleme yapılırken güncel Türk ve yabancı mahkeme kararları ile mukayeseli hukuk hükümlerine de yer verilmektedir. Tezin son bölümü olan üçüncü bölümde ise rüşvet suçuna teşebbüs, iştirak, içtima, soruşturma ve kovuşturma usulü ile rüşvet suçunun benzer suçlarla ilişkisi incelenmektedir. Ayrıca yine bu bölümde kamu idaresi dışında işlenen rüşvet suçu ile yabancılık unsuru taşıyan rüşvet suçuna ilişkin bilgiler verilmektedir.

In this dissertation, the bribery offense, in the article 252 of Turkish Criminal Code Numbered 5237 is examined.Thedissertationconsists of threeparts.In the first part, the concept of public administration which is the interlocutor of the bribery offense, the regulation of the crimes against the public administration in the criminal laws, the concept of bribery in general, the types of the bribery crime, the legal benefits protected by the bribery offense, the historical development of the crime are examined.The first part also contains the current provisions in the Turkish criminal law and comparative law concerning the bribery offense.In the second part, which is the main body of the dissertation, the structure and elements of the bribery offense are examined in full detail.When examining, current Turkish and foreign court decisions and comparative law provisions are also included.The third part, which is the last section of the dissertation, examines the attempt of bribery offense, mixedoffences, participation, investigation and prosecution and the relationship of bribery offense with similar crimes.Moreover, this part also provides information on bribery offense in the private sector and bribery offense carrying foreign elements.
Keywords: Bribery; Cezai soruşturma; Criminal investigation; Duty; Görev; Görevi kötüye kullanma; Haksız Menfaat Public Administration; Kamu Görevlisi; Kamu hukuku; Kamu İdaresi; Law and legislation; Misconduct in office; Political corruption; Public law; Public Official; Rüşvet; Siyasi suistimal; Turkey; Türkiye; Unfair Benefit; Yasa ve yasama